ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN AUDITOR (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2008 – 2012) - Nikmah, Latifatun; Nur Rahardjo, Shiddiq (Diponegoro Journal of Accounting, 2014)
The purpose of this research is to find empirical proof concerning factors that might influence auditor switching in Indonesia. Some of past research about factors that influence auditor switching still shows different results. Therefore, another research needs to retest the theory of auditors switching.The population in this research are all of the manufacturing companies listed on the Indonesia Stock Exchange and continously published financial statements in 2008 – 2012. Based on purposive sampling method, samples obtained by 70 companies in the period 2008 – 2012 so obtained 350 data observations. Hypothesis in this research are tested by logistic regression analytical method. Research variable being used are Accounting Firm Size (KAP), Audit Opinion (OPINI), Management Turnover (CEO), Financial Distress (FD), Percentage Independent Commissioner (IDK), and Auditor Switching (SWITCH). The result of this research show that: (1) Accounting Firm Size has significant effect on Auditor Switching, (2) Audit Opinion does not have significant effect towards Auditor Switching, (3) Management Turnover does not have significant effect towards Auditor Switching, (4) Financial Distress has significant effect towards Auditor Switching, and finally (5) percentage independent commissioner does not have significant effect towards Auditor Switching